A STUDY ON THE GEOPOLYMERIZATION KINETICS OF FLY ASH BASED GEOPOLYMER - SIYAL, AHMER ALI (2015)
Geopolymers are versatile materials possessing properties superior to conventional materials as well as potential of use in a variety of applications. Geopolymerization is a multistep process involving many reactions occurring concurrently. Despite several kinetics studies, the geopolymerization kinetics of fly ash based geopolymers and the mechanism involved during its formation has not been well understood. This research determines the geopolymerization kinetics of fly ash based geopolymer using Kolmogorov-Johnson-Mehl-Avrami (KJMA) model and characterization techniques. The geopolymer formation with time was measured in terms of degree of reaction of fly ash (a)byhydrochloric acid (HC1) method. Four synthesis parameters such asNa/Al ratio (1-1.4), Si/Al ratio (1.8-2.6), W/S ratio (0.2-0.3), and curing temperature (40- 80°C) were selected to determine their effects on setting time, compressive strength, and degree of reaction (a).